Online-BSEE (Online Bachelor of Science in Electrical Engineering): An Asynchronous Online Electrical Engineering Degree Program with Laboratory. (June 2014) - Tang, Wendy; Westgate, Charles; Liu, Pao-Lo; Gouzman, Michael
The Online Bachelor of Science in Electrical Engineering is a collaborative effort among three University Centers at SUNY (State University of New York), namely Stony Brook, Binghamton, and Buffalo. The program delivers the complete electrical engineering curriculum at the bachelor level to students online and asynchronously. Students, however, take the basic mathematics and science courses and general education courses elsewhere (online or at local institutions). It is one of the first such programs nationwide. More specifically, online electronic laboratory courses are delivered online with students performing the same experiments as those in traditional offerings. This is made possible via innovative use of technology. Further, through insights developed in the initial offering, a new laboratory kit is being designed. Finally, some of our online lectures developed in the program are also being used to supplement and enrich on-campus offerings, hence creating a win-win approach.